European expert consensus statement on therapeutic goals in Fabry disease - Wanner, Christoph; Arad, Michael; Baron, Ralf; Burlina, Alessandro; Elliott, Perry M.; Feldt-Rasmussen, Ulla; Fomin, Victor V.; Germain, Dominique P.; Hughes, Derralynn A.; Jovanovic, Ana; Kantola, Ilkka; Linhart, Ales; et al. (Molecular Genetics and Metabolism, 2018)
Background: Fabry disease, an inherited lysosomal storage disorder, causes multi-organ pathology resulting in substantial morbidity and a reduced life expectancy. Although Fabry disease is an X-linked disorder, both genders may be affected, but generally to a lesser extent in females. The disease spectrum ranges from classic early-onset disease to non-classic later-onset phenotypes, with complications occurring in multiple organs or being confined to a single organ system depending on the stage of the disease. The impact of therapy depends upon patient- and disease-specific factors and timing of initiation. Methods: A European panel of experts collaborated to develop a set of organ-specific therapeutic goals for Fabry disease, based on evidence identified in a recent systematic literature review and consensus opinion. Results: A series of organ-specific treatment goals were developed. For each organ system, optimal treatment strategies accounted for inter-patient differences in disease severity, natural history, and treatment responses as well as the negative burden of therapy and the importance of multidisciplinary care. The consensus therapeutic goals and proposed patient management algorithm take into account the need for early disease-specific therapy to delay or slow the progression of disease as well as non-specific adjunctive therapies that prevent or treat the effects of organ damage on quality of life and long-term prognosis. Conclusions: These consensus recommendations help advance Fabry disease management by considering the balance between anticipated clinical benefits and potential therapy-related challenges in order to facilitate individualized treatment, optimize patient care and improve quality of life.
EVALuna2:207471